Validitas Model Inkuiri yang Diintervensi Proses Reflektif untuk Melatih Kemampuan Berpikir Kritis Mahasiswa Calon Guru - Ni Nyoman Sri Putu Verawati; Hikmawati Hikmawati (IKIP Mataram, 2019)
The Validity of the Inquiry Model Intervened by the Reflective Process to Facilitate Preservice Teachers' Critical Thinking Ability. Critical thinking has become the main competency of 21st century learning and encourages the development of learner critical thinking at the higher education level regarded as an important outcome of education. This study develop an inquiry learning model which are intervened by reflective processes in their teaching, or in its development called Reflective-Inquiry Learning (RIL) Model which is specifically aim to improve critical thinking ability of preservice teachers. This research is the first step in development research in which the RIL model developed was constructed based on theoretical and empirical studies so that it gave birth to a hypothetical framework of the RIL model itself. The RIL model product was then validated by involving 7 experts as validators through the focus group discussion (FGD) mechanism. Validation aspects include content validity and construct validity. The data from the validation of the model were analyzed descriptively by averaging the results of validation. The validation results of the RIL model show that the validity level (Va) of 4.28 in a very valid category. Whereas Va in the content validity and construct validity aspects are 4.26 and 4.32, both in the very valid category. The hypothetical framework model developed based on the conceptual frame and the results of its validation is provided in this article.